Проблемы исследования поэднеантичных боспорских расписных склепов - Зинько, Е.А. (Материалы по археологии, истории и этнографии Таврии, 2001)
Позднеантичные боспорские расписные склепы расположены среди довольно компактной группы погребальных сооружений этого типа на некрополе Пантикапея- Боспора на северном склоне горы Митридат, доминирующей над центральной частью современного города Керчи. Late Antique Bosphoros painted vaults are within rather a compact group of burial constructions of this type in the necropolis of Panticapeum - Bosphoros on the northern slope of the mountain of Mithradates, dominating over the central part of the modern city of Kerch. P. Dubriux started to research these monuments as early as in 1816-1818. During the following years the directors of Kerch museum and the members of Imperial Archaeological Commission revealed 200 vaults all in all. Most of them were robbed and only some of them attracted attention with their wall painting. M. I. Rostovtseff summed up the results of investigations of the 19th - the beginning of the 20th centuries in his monograph “Ancient decorative painting in the South of Russia” which is still the most complete collection of known monuments. According to M. I. Rostovtseff in Kerch there were 9 late antique vaults with wall painting of geometric style. All these vaults in location, architecture, character of wall painting, dating and religious representations are closely connected with the cult of Sabazios.